2018
DOI: 10.1002/maco.201810485
|View full text |Cite
|
Sign up to set email alerts
|

KMnO4‐system etching process and electroless nickel plating on ABS

Abstract: Etching treatment for acrylonitrile butadiene styrene (ABS) resin and electroless nickel plating process have been studied. The ABS first was etched in a chromium‐free potassium permanganate etching system with different etching times. Scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT‐IR), and hydrophilicity test showed that the ABS is of moderate and homogeneous hole size after being etched at a temperature of 65 °C with 6 g L−1 potassium permanganate for 20 min. Then electroless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The CFRP samples were etched by immersion in a solution containing 0.2 M KMnO 4 + 4 M NaOH at 373 K for 45 min. 15) After the etching, the samples were sulfonated by immersion in a solution containing 14 M H 2 SO 4 at 333 K for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The CFRP samples were etched by immersion in a solution containing 0.2 M KMnO 4 + 4 M NaOH at 373 K for 45 min. 15) After the etching, the samples were sulfonated by immersion in a solution containing 14 M H 2 SO 4 at 333 K for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…This method had potential applications in composite material synthesis and intermediate pattern fabrication, although further research was necessary to enhance adhesion between substrates and coatings. In a study, 89 ABS substrate was etched for nickel electroless plating process using a chromium‐free potassium permanganate (KMnO 4 ) solution, resulting in consistent and moderate hole sizes at a temperature of 65°C using a solution of 6 g/L potassium permanganate for a duration of 20 min. Subsequently, electroless nickel plating took place at a temperature of 45°C and a pH range of 8.5–9.5.…”
Section: Metallization Techniquesmentioning
confidence: 99%
“…According to kinetic studies, it was possible to obtain a Ni thickness of around 2 μm in 2 h. Additionally, a proof-of-concept experiment showed that Ni-coated polymer sheets may be electroplated with a variety of metals, including copper (Cu), to achieve a thickness of approximately 15 μm in just 1 h of electrodeposition. This method had potential applications in composite material synthesis and intermediate pattern fabrication, although further research was necessary to enhance adhesion between substrates and coatings.In a study,89 ABS substrate was etched for nickel electroless plating process using a chromium-free potassium permanganate (KMnO 4 ) solution, resulting in consistent and moderate hole sizes at a temperature of 65 C using a solution of 6 g/L potassium permanganate for a duration of 20 min. Subsequently, electroless nickel plating took place at a temperature of 45 C and a pH range of 8.5-9.5.…”
mentioning
confidence: 99%
“…In the last decade, there have been a very intensive quest for improving the etching treatment for ABS especially for copper and nickel plating. 19,21,22 There are many different alternatives proposed in these studies and all of them with the same target, avoid the use of Cr 6+ in metallization of ABS and other polymers. 22 The studies focused in substituting the sulfuric-chromic acid bath, and among many different procedures, the use of KMnO 4 have been one of the more important points of reference.…”
Section: Introductionmentioning
confidence: 99%
“…22 The studies focused in substituting the sulfuric-chromic acid bath, and among many different procedures, the use of KMnO 4 have been one of the more important points of reference. 21,23 Nowadays, the swelling of substances into polymers are mainly used in hydrogels for making of them superabsorbent composites 24 and conferring them some characteristics by the swelling of substances such as ionic, 25,26 anti-microbial, 27 fuels, 28 fertilizers. 29 There are other works focused in the humidity absorption into polymers.…”
Section: Introductionmentioning
confidence: 99%